Toxic and essential metals in Cyprinus carpio, Carassius gibelio, and Luciobarbus esocinus tissues from Keban Dam Lake, Pertek, Turkey - Kaya, Gokce; Turkoglu, Semra (Taylor & Francis Ltd, 2018)
In various tissues of Luciobarbus esocinus, Cyprinus carpio, and Carassius gibelio which were taken from Keban Dam Lake Pertek region's freshwaters, Turkey in January-February 2016, concentrations of mercury, nickel, lead, cadmium, arsenic, manganese, chromium, and cobalt were analysed by inductively coupled plasma-mass spectrometry (ICP-MS) after microwave digestion. In fish muscle mean chromium concentration (0.614mg kg(-1) in C. carpio muscle) was higher than the maximum limits as set by the Federal Environmental Protection Agency and World Health Organisation. Additionally, mean concentration of lead (0.380mg kg(-1) in C. gibelio muscle) was higher compared to the maximum limit as set by Turkish Standards. Furthermore, in the assessment of the potential health risk, estimated weekly and daily intake of all metals were considerably below permissible tolerable weekly intake (PTWI) and permissible tolerable daily intake values. As a result, consumption of these fish species from this region does not pose a problem on human health.
Keywords: Heavy metal; Luciobarbus esocinus; Cyprinus carpio; Carassius gibelio; Keban Dam Lake; public health risk assessment